Green credit policy and firm’s labor productivity: evidence from Chinese heavily-polluting enterprises - Lan, Yong; Zhang, Shuangshuang; Zhou, Ping; Li, Hailing; Dong, Xuesong (Frontiers in Environmental Science, 2024)
Taking the “Green Credit Guidelines” (also known as “Green Credit Policy”, GCP) in 2012 as a quasi-natural experiment, this study adopts the panel datasets between 2010 and 2019 for Chinese manufacturing firms listed publicly to examine the effects of GCP on the labor productivity of Chinese heavily-polluting companies. The findings indicate that: (1) Upon introducing GCP, it can improve labor productivity of Chinese heavily-polluting companies, a result of the promotion effect of GCP on commercial credit and technological innovation. (2) The implementation of GCP can enhance the commercial credit of Chinese heavily-polluting enterprises and relieve its financing constraints to some degree. (3) The implementation of GCP can further the innovation activities of Chinese heavily-polluting companies and realize the re-test of the “Porter effect”. (4) The heterogeneity test indicates that GCP exerts a pronounced promoting influence on state-owned and large heavily-polluting enterprises in eastern China. Those conclusions are still valid after robustness tests. This research offers empirical evidence and policy wisdom for promoting the green conversion of manufacturing enterprises.